Harnessing electroosmotic hybrid nanofluid dynamics in curved arteries: insights into biomedical flow enhancement - El Kot, M. A.; Alsharif, Abdullah Madhi; Abd Elmaboud, Y.; Abdelsalam, Sara I. (Frontiers in Nanotechnology, 2024)
In this study, we investigated the dynamics of unsteady electroosmotic pulsatile flow involving a hybrid nanofluid within a curved artery, influenced by both stenosis and an embedded catheter. The hybrid nanofluid, a mixture of silver (Ag) and aluminum oxide (Al2O3) nanoparticles dispersed in blood, was modeled via the Carreau non-Newtonian framework to more accurately represent the intricate nature of blood flow. The electroosmotic forces introduced simulated the effect of an external electric field, while the catheter served as an additional structural constraint within the artery. To account for both the curvature of the vessel and the overlapping stenosis, we derived the governing equations for this model. Using numerical methods, particularly the finite-difference approach, we solved the nonlinear partial differential equations that govern the flow, temperature, and concentration distributions. Our findings suggest that the hybrid nanofluid demonstrates enhanced thermal and flow properties compared to standard fluids. The results showed significant influences from electroosmotic forces, curvature, and pulsatility on the velocity, temperature, and concentration profiles. Furthermore, an increase in the electroosmotic and Weissenberg parameters substantially accelerated fluid velocity by reducing viscous drag while improving mass transport. These results offer valuable insights into the behavior of blood flow in catheterized arteries and may inform future advancements in cardiovascular treatment technologies.